2008
DOI: 10.1002/elps.200800211
|View full text |Cite
|
Sign up to set email alerts
|

Quantitative assessment of human serum high‐abundance protein depletion

Abstract: The aim of this study is to quantify the effectivity of the depletion of human high-abundance serum and plasma proteins for improved protein identification and disease marker candidate discovery and to assess the risk of concomitant removal of relevant marker proteins. 2-DE and bottom-up shotgun MS combining 2-D capillary chromatography with MS/MS were applied in parallel for the analysis of fractions resulting from the depletion procedure. For many proteins the factors of enrichment by the depletion were obvi… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

2
41
0

Year Published

2010
2010
2017
2017

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 50 publications
(44 citation statements)
references
References 61 publications
2
41
0
Order By: Relevance
“…There may well be low affinity interactions by many proteins with the lipids on the surface of albumin. Recent experiments that claim to exploit albumin binding lacked control comparisons to demonstrate the proportion of binding that results from low-affinity interactions with albumin and the proportion of non-specific interactions with the chromatography resin (Lopez et al, 2005;Lowenthal et al, 2005;Stempfer et al, 2008;Lai et al, 2009). Controlled experiments to date have not conclusively shown high affinity interacting proteins associated with albumin (Marshall et al, 2003Zhang et al, 2004;Tucholska et al, 2007Tucholska et al, , 2009Williams et al, 2007) analogous to those clearly demonstrated with apolipoproteins .…”
Section: Albuminmentioning
confidence: 81%
See 3 more Smart Citations
“…There may well be low affinity interactions by many proteins with the lipids on the surface of albumin. Recent experiments that claim to exploit albumin binding lacked control comparisons to demonstrate the proportion of binding that results from low-affinity interactions with albumin and the proportion of non-specific interactions with the chromatography resin (Lopez et al, 2005;Lowenthal et al, 2005;Stempfer et al, 2008;Lai et al, 2009). Controlled experiments to date have not conclusively shown high affinity interacting proteins associated with albumin (Marshall et al, 2003Zhang et al, 2004;Tucholska et al, 2007Tucholska et al, , 2009Williams et al, 2007) analogous to those clearly demonstrated with apolipoproteins .…”
Section: Albuminmentioning
confidence: 81%
“…Considering the capacity of a typical nano-LC column coupled with LC-MS/MS is on the order of 1 mg or less, the dilute product is still sufficient for direct analysis even after separation of digested peptides. There is evidence of non-specific binding of proteins to these depletion columns (Stempfer et al, 2008) with mixed results regarding the reproducibility of depletion column (Dekker et al, 2007;Seam et al, 2007). There is still a concentration range of 7-8 orders of magnitude after elimination of high abundance proteins (Linke, Doraiswamy, & Harrison, 2007).…”
Section: Depletion Chromatographymentioning
confidence: 90%
See 2 more Smart Citations
“…Depletion of the highly abundant proteins was also found detrimental in the phosphoproteome analysis of CSF (26). Indeed, off-target removal was reported using albumin-specific and other immunodepletion kits (31)(32)(33). This may be because of the role of albumin as a cargo for various compounds or a result of nonspecific binding to the affinity matrix.…”
mentioning
confidence: 99%